The Role of Digital Technologies for Project Representation (diségno, 2018)
In recent years construction industry is crossing an innovation process based on the digitization of information to reliably describe the existing architectural heritage. Therefore, the need to adopt a new graphic language based on information modelling that summarises graphic and alphanumeric characteristics of a certain building has emerged. This contribution focuses on the analysis of aspects that have characterized the idea of representation in the past, proposing information modeling as a natural renewal of design representation through digital technologies.
Keywords: Drawing; 3D parametric; modelling; BIM; Existing building